Flowability and compressive strength of ternary blended cement mortar of coal bottom ash and ground cockle shell ash - Nabilla, Mohamad; Rahimah, Embong; Nor Hazurina, Othman; Khairunisa, Muthusamy; Mohd Faizal, Md Jaafar (TULPAR Academic Publishing, 2025)
Flourishing cement industry to meet the demand of construction industry has negative impact to the global environment owing to the carbon emission during calcination of cement. At the same time, the disposal of coal bottom ash and cockle shell from coal power plant and cockle trade which pollutes the environment also need to be resolved. In view of circular economy, the present research aims to produce ternary blended cement consisting of coal bottom ash (CBA) and cockle shell ash (CSA) for sustainable mortar production. The research was conducted to determine the effect of CBA as partial cement replacement on flowability and compressive strength of CSA blended cement mortar. Seven mortar mixes consisting of CBA as supplementary cementitious material ranging from 0% to 60% by weight of cement were prepared. All specimens were water cured up to 56 days. The flowability test was conducted to assess the properties of the fresh state, while hardened properties were evaluated through compressive strength test at 1, 3, 7, 28, and 56 days. The results showed flowability decreased by 5% to 31% with increasing CBA content compared to the control mix. The use finer sized CBA forms a slightly stickier mortar mix with lower flowability. A combination 10% to 20% CBA is the best percentage to use for formation of CSA mortar with enhanced strength. However, a maximum strength of 23 MPa was achieved at 56 days with an optimal CBA replacement of 10%. This research demonstrates the potential by transforming industrial waste for low-carbon cement production to save the use of landfills for waste disposal and optimize consumption of non-renewable resources